Investigation on potential malaria vectors (Anopheles spp.) in the Province of Trento, Italy - Tagliapietra, Valentina (Malar J, 2019)
BACKGROUND: Europe and Italy were declared malaria free since the 1970s although the presence of competent vectors and the high number of yearly imported malaria cases make this disease a potential rising health issue. In September 2017, a cryptic fatal case of Plasmodium falciparum malaria in the Province of Trento, Italy, raised the concern of health authorities on the possible resurgence of this disease in the Mediterranean Basin. METHODS: An entomological surveillance by means of BG traps, CDC light traps and larval search was performed. Sites were chosen among urban and suburban environments (e.g. private houses, public parks, schools, cemeteries, ecotone urban/forest, farms), ranging from an altitude of 91 to 1332 m above sea level. All the mosquitoes collected were morphologically identified and about half of them (103; 49%) were confirmed with the sequencing analysis of the rRNA internal transcribed spacer 2 (ITS-2). RESULTS: In the present study 287 sites were screened for the presence of Anopheles spp. and 211 specimens were collected and identified. Hundred-eighteen individuals (56%) belonged to Anopheles plumbeus, 56 (26.5%) to Anopheles maculipennis complex, 10 (4.7%) to Anopheles claviger and 27 were identified only at genus level. This is the first record for the presence of An. plumbeus in the study area. CONCLUSIONS: The presence of Anopheles spp. mosquitoes in the Province of Trento, Italy, has been updated with the occurrence of An. plumbeus. The risk of malaria endemicity in the area is to be considered very low, but urban and peri-urban habitat may act as potential breeding sites for the presence of mosquito vectors and should be constantly monitored.